Educação artística informal e criação de públicos : os casos Caldas Late Night, e Comboio de Lata, na perspectiva da arte relacional - Vieira, Sara dos Santos, 1998- (2015)
Art is the intimate poetics of the human being. By art, and through art Man understands the connections that link us to the world; art dissertations reflect the patterns, conceptions and problems that interpellate Man. The transformations that occur in the artistic domain, including its principles and dynamics, highlight the watchful eye of the cultural agents. This research aimed at understanding the contemporaneous problems that bind the artistic reality; the place occupied by art, and the dissertations that materialize it, represent the main issues. This research is based on the problems, conceptions and theories concerning the place of art, comprehending the exhibition space, the cultural agents where we include the cultural dissertation and the dissemination platforms, and the principles of relational aesthetics. The methodology of the case study, applied to two cultural and artistic phenomena: Caldas Late Night and Marinha a tempo e horas (“Marinha on Time”), allowed a better understanding of the ideological principles that promote the emergence of art, as well as its dissertations. Summarizing, we can conclude that art interposes itself through its singular way of transforming the social body into an organic whole; through its exceptional ability to regenerate, rehabilitate and restructure society